Kajian Estetika Visual dan Makna Simbolik dalam Karya Seni Lukis Bejo Prichatianto Seniman Kabupaten Batang - Rizki Tri Hardi; Mujiyono (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to examine the visual aesthetics and symbolic meaning in the paintings of Bejo Prichatianto, an artist from Batang Regency. The study is motivated by the fact that paintings not only possess visual beauty but also contain symbols and messages that represent personal experiences, cultural values, and the social life of the community. This research employed a descriptive qualitative method using aesthetic and semiotic approaches. The aesthetic analysis was based on A.A.M. Djelantik’s theory, which explains that aesthetic value consists of form, content, and presentation, while the semiotic analysis referred to Charles Sanders Peirce’s theory of signs and symbolic meaning. Data were collected through interviews, documentation, and literature review of Bejo Prichatianto’s artworks. The findings indicate that Bejo Prichatianto’s paintings exhibit distinctive aesthetic characteristics reflected in the harmonious use of color, composition, texture, and visual forms. Furthermore, the symbols embedded in the paintings convey meanings related to community life, local cultural values, and the artist’s emotional expression. Therefore, Bejo Prichatianto’s paintings represent an artistic expression of personal experiences, local culture, and social realities manifested through visual aesthetics and symbols with profound meanings.